Self-medication for acne among undergraduate medical students - Varshaben Vejabhai Karamata; AM Gandhi; PP Patel; MK Desai (Indian Journal of Dermatology, 2017)
Aims: This study aims to evaluate the knowledge and pattern of self-medication for acne among undergraduate medical students at a tertiary care teaching hospital. Materials and Methods: This cross-sectional study was conducted in II MBBS (Group A), III MBBS Part I (Group B), and III MBBS Part II (Group C) students. Prevalidated questionnaire about knowledge, attitude, and practice of self-medication were administered to participants. Data were analyzed using one-way analysis of variance and Chi-square test. Results: Out of 582 students who responded to questionnaire, 518 suffered from acne. Self-medication practice was observed in 59.2% students. Significantly higher number of female students practiced self-medication (P < 0.0001). Most common source of information was seniors/friends/family members (34.2%). The mildness of illness (42.3%) was the most common reason of self-medication. A total mean score of knowledge was significantly higher in Group C as compared to Group A (P < 0.001) and Group B (P < 0.05). Allopathic medication was preferred by 69.8% students. Seventy-five percentage students read leaflet/package insert/label instruction and expiry date of the medicines. Conclusions: The participating students lack the knowledge about self-medication for acne. Adequate knowledge and awareness about the appropriate use of medication will reduce the practice of self-medication and improve rational prescribing.